Bridging the Gap: How Technology Integration is Transforming the Classroom Experience - Haidir, Nurul Khatimah Haidir (Universitas Terbuka, 2023)
In the ever-evolving landscape of education, the integration of technology into teaching and learning has emerged as a transformative force, reshaping the classroom experience in profound ways. This study aims to investigate the EFL teachers’ perceptions on ICT in English classrooms. The participants involved in this research were four English language teachers from two junior high schools in Parepare city. The study results shoed that all participants had a positive perception about the use of ICT in English classrooms. The results also showed that the English language teachers supported the existence of ICT in English Classroom which is claimed to be helpful. However, they still had barriers in applying ICT in their classroom technically and non-technically.